Volatile constituents of vetiver: a review†. (January 2015) - Belhassen, Emilie; Filippi, Jean‐Jacques; Brévard, Hugues; Joulain, Daniel; Baldovini, Nicolas
ABSTRACT A comprehensive and critical compilation of the volatile constituents of vetiver root (Chrysopogon zizanioides L.) is presented, including those present in its essential oil. This extremely complex material has stimulated analytical research for many decades in the hope of unravelling the secrets of its composition. Up to now, more than 300 molecules have been reported, mostly sesquiterpenoids possessing a large variety of skeletons, together with their norterpenic counterparts. This review attempts to clarify some of the discrepancies related to the characterization of these constituents, which were often due to the misuses of analytical methods without enough critical consideration of the literature. The identification of the main odour impact components of vetiver is also discussed, because much contradictory information appears in the literature on this subject. Copyright © 2014 John Wiley & Sons, Ltd.